Environmental Policies, Agencies and Flood Management in Selected States in Nigeria (2005-2021): The Gaps and The Challenges - Oni, Michael Abiodun; Ayegba, Sunday (NIU Journal of Humanities, 2022)
Floods have affected the lives of people across the world. Nigeria is not an exception. It has resulted in the loss of lives, damage to infrastructure, agricultural produce and disruption of social life. In addressing the problem, Government has formulated and implemented different policies, set up various agencies to mitigate the devastating effects in the last fifteen years, In spite of these efforts, the problem of flooding continues, unabated in Nigeria. Hence this study investigated the influence of government environmental policies and government agencies on flood management in Nigeria. Mixed method design was adopted for the study. The population of the study was 990. Taro Yamani formulae was used to determine the sample size of 285. Purposive and stratified sampling was adopted in the location of the respondent. Questionnaire and interview guides were used for the study. Data collected were analyzed using descriptive and inferential statistics while the qualitative data were content analyzed. The study found that the flood management mechanisms of agencies had no significant effect on flood management (Adj. R 2 = 0.011:F(1,258) = 2.737, P>0.05). The content analysis revealed that government environmental policies in the study area in the last 15 years have not been adequately implemented. The study recommended that the Federal Government should review government environmental policies in the study areas. The study also recommended the setting up of a new dedicated and centralized agency for effective flood risk management in Nigeria. Keywords: Flood Management, Environmental policy, flood disasters, government agencies.